2011
DOI: 10.3171/2011.7.spine10887
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding abdominal flank bulge after anterolateral approaches to the thoracolumbar spine: cadaveric study and electrophysiological investigation

Abstract: Object The thoracolumbar junction is frequently accessed through an anterolateral approach with the incision and muscle dissection extending from the lower thoracic region to the lateral border of the rectus abdominis muscle. This approach is frequently associated with the subsequent development of an unsightly and uncomfortable relaxation of the ipsilateral abdominal wall, or flank bulge, caused by denervation injury to the intercostal nerves. However, the etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…This finding is supported by an anatomical study of the innervation of the lateral abdominal wall in cadavers demonstrating that the 3 lateral muscle layers EO, IO, and TA are primarily innervated by branches from T12 and L1. 15 The clinical effect of this relaxation is still unknown, but muscle relaxation may be part of the pain-relieving effects reported in clinical studies. Pain originating from deeper structures than the skin may play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by an anatomical study of the innervation of the lateral abdominal wall in cadavers demonstrating that the 3 lateral muscle layers EO, IO, and TA are primarily innervated by branches from T12 and L1. 15 The clinical effect of this relaxation is still unknown, but muscle relaxation may be part of the pain-relieving effects reported in clinical studies. Pain originating from deeper structures than the skin may play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…14 In cadaveric dissections and intraoperative electromyography studies, T11 and T12 were found to be responsible for abdominal wall innervation in 81% to 97% of patients. 15 Clinical reports have given support to anatomical studies, as preservation of T11 and T12 through electromyography monitoring results in preservation of the abdominal musculature postoperatively. 15 Furthermore, reports of temporary, reversible lateral abdominal bulge after infiltration of local anesthetic into the transversus abdominus plane block 16,17 and bulge after postherpetic neuralgia occurring in the T11 and T12 dermatomal distributions further support the importance of the T11 and T12 nerves in anterolateral abdominal wall innervation.…”
Section: Discussionmentioning
confidence: 92%
“…15 Clinical reports have given support to anatomical studies, as preservation of T11 and T12 through electromyography monitoring results in preservation of the abdominal musculature postoperatively. 15 Furthermore, reports of temporary, reversible lateral abdominal bulge after infiltration of local anesthetic into the transversus abdominus plane block 16,17 and bulge after postherpetic neuralgia occurring in the T11 and T12 dermatomal distributions further support the importance of the T11 and T12 nerves in anterolateral abdominal wall innervation. 18 Standard flank incisions result in postoperative bulge rates up to 57%, 5 and demonstrate greater volumetric bulge, paresthesia, and numbness.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…14,15 Flank bulge due to laxity of the anterolateral abdominal musculature may be caused by damage to intercostal nerves. 14 In a cadaveric and electrophysiological study, Fahim and colleagues showed that the most significant intercostal nerve contributions to the anterolateral wall came from the T11 and T12 nerves.…”
Section: Discussionmentioning
confidence: 99%